Health and recreational physicalactivity in modern society: essence, functions and development prospects - Kovtun, A. (Sportyvnyi Visnyk Prydniprovia, 2025)
Introduction. In modern society, the problem of preserving and strengthening the health of the population is becoming increasingly relevant due to the spread of hypokinesia, high morbidity rates, and a decline in the physical fitness of different age groups. In this context, health and recreational physical activity, which integrates health, preventive, and restorative aspects of physical culture, is of particular importance. However, both in international and domestic scientific literature, there is a lack of unified terminology, which complicates the standardization of research and the practical implementation of relevant programs. The purpose of the study is to theoretically sub-stantiate the essence and functions of health and recreational physical activity, as well as to determine the prospects for its development in modern society. Research methods.To achieve the stated aim, a set of scientific methods was applied, including theoretical analysis and generalization of literary sources, comparative analysis, systematization, and classification. Research results. The analysis of scientific sources showed that the concept of «health-improving and recreational physical activity» integrates international concepts such as physical activity, leisure-time physical activity, recreational physical activity, and health-enhancing physical activity, as well as Ukrainian scientific approaches. The proposed general definition is interpreted as a specific form of physical activity carried out in free time or in the context of organized events, with optimal parameters of volume and intensity, aimed at strengthening physical and mental health, preventing diseases, and improving the quality of life. The functions of health-improving and recreational physical activity were systematized, including health-promoting, restorative, psycho-hygienic, social-communicative, cultural-leisure, and educational functions. The prospects for the development of this phenomenon were identified in the areas of technological innovation, medical and rehabilitation integration, educational strategies, social inclusion, environmental adaptation, and global public health policy. Conclusions. The generalization of scientific approaches made it possible to formulate a comprehensive definition of health and recreational physical activity and to identify its functions as a multidimensional phenomenon that integrates biological, psycho-emotional, social, and cultural aspects. Further research should be directed toward the practical integration of health and recreational physical activity into educational programs, rehabilitation systems, inclusive social projects, and related initiatives.